Combined pulmonary fibrosis and emphysema characteristics in a Greek cohort. Issue 1 (18th March 2019) - Malli, Foteini; Papakosta, Despoina; Antoniou, Katerina; Dimadi, Maria; Polychronopoulos, Vlassis; Malagari, Katerina; Oikonomou, Anastasia; Bouros, Demosthenes E.; Daniil, Zoe
Background: Combined pulmonary fibrosis and emphysema (CPFE) has recently received great attention, with studies suggesting that it presents a distinct clinical entity while others have challenged this hypothesis. This nationwide study aimed to describe a large cohort of Greek CPFE patients and to examine potential prognostic factors for survival. Methods: This retrospective study included 97 patients with CPFE. Demographic and clinical data, pulmonary function tests, echocardiography results and bronchoalveolar lavage analysis were recorded. Results: Most patients were male (94.8%) and 92% were current or ex-smokers. Spirometry results were abnormal (forced vital capacity (FVC) 72.9±19.9% pred and forced expiratory volume in 1 s/FVC 82.9±9.7%) with reduced diffusing capacity of the lung for carbon monoxide ( D LCO ) (42.3±17.4% pred). Mean systolic pulmonary arterial pressure was 41.9±19.7 mmHg and pulmonary hypertension was present in 58.8% of patients. Mean 6-min walk distance was 335.4±159.4 m. Mean emphysema score was 14.23±8.69% and mean interstitial lung disease (ILD) extent was 39.58±19.82%. Mean survival was 84 months (95% CI 72–96 months). Patients with D LCO ≥39% pred had better survival than patients with D LCO <39% pred (p=0.031). Patients with ILD extent ≥30% had worse survival than patients with ILD extent <30% (p=0.037). Conclusions: Our results indicate that CPFE patients have preserved lung volumes associated with disproportionately reduced D LCO, while reduced D LCO and increased ILD extent was associated with worse prognosis. Prognosis of CPFE is associated with pulmonary function status and ILD extent http://ow.ly/izvd30nHFgh